INTERNALIZATION OF ISLAMIC VALUES INTO ENGLISH TEACHING MEDIA (SONGS)FOR TEACHING ENGLISH IN PESANTREN - maisarah, maisarah (JURNAL SMART, 2018)
This current research is to modify songs for teaching English vocabulary by inserting Islamic values (sholawat) in them. The Hannafin and Peck Model was applied. The first phase reveals thatPesantren are mostly characterized by Islamic values and santrisâ main weaknesses concern with basic English vocabularies and pronunciation. In the second phase,the sholawat songs the santris liked were modified to teachirregular verbs and uncountable nouns. The songs were chosen because most of the santris had already been familiar with them. The third indicated that the santris gave positive responses to the songs and could remember the vocabularies easily.